Trends in caesarean section rates in Europe from 2015 to 2019 using Robson's Ten Group Classification System: A Euro-Peristat study - Amyx, Melissa; Philibert, Marianne; Farr, Alex; Donati, Serena; Smárason, Alexander K; Tica, Vlad; Velebil, Petr; Alexander, Sophie; Durox, Mélanie; Elorriaga, Maria Fernandez; Heller, Günther; Kyprianou, Theopisti; et al. (BJOG, 2024)
OBJECTIVE: To assess changes in caesarean section (CS) rates in Europe from 2015 to 2019 and utilise the Robson Ten Group Classification System (TGCS) to evaluate the contribution of different obstetric populations to overall CS rates and trends. DESIGN: Observational study utilising routine birth registry data. SETTING: A total of 28 European countries. POPULATION: Births at ≥22 weeks of gestation in 2015 and 2019. METHODS: Using a federated model, individual-level data from routine sources in each country were formatted to a common data model and transformed into anonymised, aggregated data. MAIN OUTCOME MEASURES: By country: overall CS rate. For TGCS groups (by country): CS rate, relative size, relative and absolute contribution to overall CS rate. RESULTS: Among the 28 European countries, both the CS rates (2015, 16.0%-55.9%; 2019, 16.0%-52.2%) and the trends varied (from -3.7% to +4.7%, with decreased rates in nine countries, maintained rates in seven countries (≤ ± 0.2) and with increasing rates in 12 countries). Using the TGCS (for 17 countries), in most countries labour induction increased (groups 2a and 4a), whereas multiple pregnancies (group 8) decreased. In countries with decreasing overall CS rates, CS tended to decrease across all TGCS groups, whereas in countries with increasing rates, CS tended to increase in most groups. In countries with the greatest increase in CS rates (>1%), the absolute contributions of groups 1 (nulliparous term cephalic singletons, spontaneous labour), 2a and 4a (induction of labour), 2b and 4b (prelabour CS) and 10 (preterm cephalic singletons) to the overall CS rate tended to increase. CONCLUSIONS: The TGCS shows varying CS trends and rates among countries of Europe. Comparisons between European countries, particularly those with differing trends, could provide insight into strategies to reduce CS without clinical indication.
Keywords: Pregnancy, Multiple; Cesarean Section; těhotenství mnohočetné; Humans; lidé; Female; Infant, Newborn; Labor, Obstetric; Evropa; Pregnancy; Parity; Europe; těhotenství; porodní děj; novorozenec; ženské pohlaví; císařský řez; parita